Hope and other punch lines - Buxbaum, Julie (2019)
"The tragic 9/11 event in NYC that changed the world, altered the life of Abbi Hope Goldstein as well as that of Noah Stern. They did not know each other back then, but they know each other now, and while Abbi is trying to move forward with her life, Noah still has unanswered questions that he believes Abbi can help answer"--
Abbi Hope Goldstein has lived almost her entire life in the shadow of the terrorist attacks of September 11: in an iconic photograph, Abbi wears a birthday crown and grasps a red balloon; just behind her, the South Tower of the World Trade Center is collapsing. Now her alter ego, Baby Hope, is the subject of internet memes, and Abbi is desperate for anonymity. Spending the summer before her seventeenth birthday incognito as a counselor at Knights Day Camp, she's psyched for eight weeks in the company of four-year-olds, none of whom have ever heard of Baby Hope. Too bad Noah Stern, whose own world was shattered on that terrible day, has a similar summer plan. When the two team up to ask difficult questions about the history behind the Baby Hope photo, is either of them ready to hear the answers? -- adapted from jacket
780L
Keywords: September 11 Terrorist Attacks, 2001 -- Juvenile fiction; Memes -- Fiction; Camp counselors -- Fiction; September 11 Terrorist Attacks, 2001 -- Psychological aspects -- Fiction; Fame -- Fiction; Loss (Psychology) -- Fiction; Camps -- Fiction; New York (N.Y.) -- Fiction